1958
DOI: 10.1172/jci103626
|View full text |Cite
|
Sign up to set email alerts
|

Contractility of Actomyosin Bands Prepared From Normal and Failing Human Hearts1

Abstract: Previous work from this laboratory has indicated that actomyosin bands prepared from heart muscle of dogs preserve undiminished contractility for one hour after the death of the animal (1). This suggested the possibility of investigating the contractile properties of actomyosin bands from human hearts obtained at autopsy. Such a study would make possible a comparison of actomyosin prepared from normal human heart muscle with that obtained from heart muscle of patients who had died of congestive heart failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1958
1958
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 13 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, Olson recently reported that when the administration of digitoxin to dogs in experimental congestive heart failure resulted in clinical improvement, the abnormally elevated intrinsic viscosity of myosin which occurs in experimental heart failure was restored to normal; however, digitoxin did not alter the viscosity of the myosin of the non-failing heart (32). On the other hand, Kako (33).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Olson recently reported that when the administration of digitoxin to dogs in experimental congestive heart failure resulted in clinical improvement, the abnormally elevated intrinsic viscosity of myosin which occurs in experimental heart failure was restored to normal; however, digitoxin did not alter the viscosity of the myosin of the non-failing heart (32). On the other hand, Kako (33).…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations of high energy phosphates have been reported to be normal in isolated, acutely failing dog hearts, guinea pig atria, and cat papillary muscles (13)(14)(15) and in chronically failing hearts from dogs with tricuspid insufficiency and pulmonary stenosis or with aortic insufficiency ( 11,16). Muscle preparations from failing canine and human hearts have shown decreased contractility (17,18) and decreased ATPase activity (19), but myofibrillar proteins from failing canine hearts have been reported to be both normal (20) and altered (21).…”
mentioning
confidence: 99%
“…So, when he left cardiac metabolism disappointed because it did not reveal a clue to the cause of nonischemic heart failure, 16 he turned to ever more molecular questions: the contractility of actomyosin threads 17 and topics including protein metabolism in hypertrophy and failure, 18 coronary microcirculation, lipid metabolism in isolated perfused coronary arteries, experimental myocardial infarction, diltiazem, perfluorochemical emulsions as oxygen carriers, lysophosphatidylcholine and atherosclerosis, NO, eNOS, prostacyclin, iNOS, oxidation products of NO, cyclooxygenase inhibitors, and many others. He published his last original article as first author in 2001 at the age of 92, on NO, prostanoids, cyclooxygenase, and angiogenesis in colon and breast cancer.…”
Section: Adding Ever More Colors To the Rainbow Of Experimental Cardimentioning
confidence: 99%